Controllable magnitude and anisotropy of the electrical conductivity of Hf3C2O2 MXene. (16th March 2017) - Zha, Xian-Hu; Zhou, Jie; Luo, Kan; Lang, Jiajian; Huang, Qing; Zhou, Xiaobing; Francisco, Joseph S; He, Jian; Du, Shiyu
Abstract: Hf3 C2 O2, a new MXene member synthesized recently, was predicted to be a semi-metal with high mechanical strength. Based on the unique electronic structure, the energy bands and electrical conductivities of the MXene under various strains are comprehensively investigated in this paper. Biaxial and two orthogonal uniaxial strains in both compressive and tensile manners are studied. Results from this study suggest that Hf3 C2 O2 shows a transition between semi-metal and semi-conductor under both biaxial and uniaxial strains. A compressive strain generally induces a larger energy overlap between the conduction band minimum and the valance band maximum, while a tensile strain reduces the energy band overlap and even opens a band gap. As a consequence, the magnitude of electrical conductivity decreases drastically from compressive to tensile strains applied. Moreover, the uniaxial strains are determined to be efficient in manipulating the anisotropy of the electrical conductivity. These data imply that the Hf3 C2 O2 MXene is a promising candidate material for devices such as strain sensors.